The Implementation of the Cooperative Learning Method Assisted by PowerPoint Media to Improve Student Achievement in Class XI on Computer Network Material - Oktavianus Turuna Gulo (Jurnal Pendidikan Vokasi Indonesia, 2023)
Most students still struggle to understand the learning material when it is delivered solely through verbal explanations without the aid of instructional media. However, the rapid advancement of technology provides valuable opportunities for educators to utilize engaging and interactive media to enhance students' interest and comprehension. This study aims to examine the effectiveness of using interactive PowerPoint media to improve the understanding of Grade XI students in learning computer network concepts. The research employed a Classroom Action Research (CAR) method, with data collected through observation, questionnaires, and testing. The subjects of this study were 14 Grade XI students and one Information and Communication Technology (ICT) teacher. The findings indicate that the implementation of interactive PowerPoint within the cooperative learning model significantly improved students' understanding. Prior to using this media, the average student score was 47.8. After implementing the interactive PowerPoint, the average score increased to 75.4, demonstrating a substantial improvement in students’ comprehension of the computer network material.